Pure epithelial neuroendocrine neoplasms of the bladder: clinicopathological characteristics of 2 cases and literature review - ZHOU Henghua, LIN Lan, ZHU Guixiang, LIU Min, HUANG Wentao (Zhenduanxue lilun yu shijian)
Objective To investigate the clinicopathological features and prognosis of pure epithelial neuroendocrine neoplasms (NEN) of the bladder. Methods A retrospective analysis was conducted on the clinical data, histopathological morphology, and immunohistochemistry of 2 patients with pure epithelial NEN of the bladder admitted between 2018 and 2024. A differential diagnosis was performed, and a detailed literature review was conducted. Results Both patients were females, aged 85 (Case 1) and 84 (Case 2), presenting with lower limb edema and hematuria, respectively. B-scan ultrasound and MRI examinations showed a polypoid hypoechoic lesion in the trigone of the bladder in Case 1, with no enhancement on MRI, suggesting a benign lesion. Case 2 showed a nodular hypoechoic lesion in the anterior bladder wall with significant enhancement on MRI, suggesting a malignant tumor, with paraganglioma not excluded. Gross examination revealed that the two cases had one polypoid tissue and one nodular tissue, respectively, with maximum diameters ranging from 0.6 cm to 3.0 cm. Case 1 had a smooth surface, while Case 2 had a grayish-yellow cross section with medium hardness. Microscopically, both tumors showed typical NEN histopathological features, with the surface covered by bladder mucosa. Case 1 was confined to the lamina propria, while Case 2 showed invasive growth into the muscularis propria. Case 1 was diagnosed as well-differentiated neuroendocrine tumor (WD-NET) and Case 2 as large cell neuroendocrine carcinoma (LCNEC). Immunohistochemically, both tumor cells diffusely expressed broad-spectrum cytokeratin and neuroendocrine markers (2/2), with wild-type expression of P53 (2/2). The Ki67 proliferation index was 3%-5% in Case 1, with focal PSAP expression, and 60%-70% in Case 2, with minimal GATA-3 expression. Neither patient received special treatment. Case 1 was followed up for 76 months with no recurrence, while Case 2 died of recurrence and lung metastasis 3 months after surgery. Literature review suggested that pure epithelial NEN of the bladder exhibited typical histopathological morphology and immunophenotype of NEN. WD-NET typically followed an indolent course, while LCNEC was highly invasive and prone to recurrence and metastasis, consistent with the two cases reported in this study. Conclusions Pure epithelial NEN of the bladder is extremely rare. The definitive diagnosis mainly relies on histopathological examination and immunohistochemical staining. WD-NET has a good prognosis after complete tumor resection while LCNEC is highly invasive and has a poor prognosis.